Chemical evidence of preserved collagen in 54‐million‐year‐old fish vertebrae. (11th January 2020) - Dutta, Suryendu; Kumar, Sumit; Singh, Hukam; Khan, Mahasin A.; Barai, Amlan; Tewari, Anuradha; Rana, Rajendra S.; Bera, Subir; Sen, Shamik; Sahni, Ashok
Abstract: Collagens are the most abundant proteins in the animal kingdom. They form the structural framework of connective tissues such as bones, tendons and skin, and play important biomechanical role in supporting tissue functions. The preservation of collagen in deep time is a topic of intense debate. Here we provide indisputable evidence for the presence of collagen in early Eocene fish vertebrae using online pyrolysis comprehensive two dimensional gas chromatography time‐of‐flight mass spectrometry (py‐GC×GC‐TOFMS) and immunofluorescence analysis. The presence of cyclic dipeptides such as diketodipyrrole, 2, 5‐diketopiperazine of proline‐proline and 2, 5‐diketopiperazine of proline‐glycine along with other nitrogen‐bearing molecules in the pyrolysis products of the studied fossils unequivocally demonstrate that collagen can withstand degradation and diagenetic alteration. Immunofluorescence study also confirms the presence of collagen‐I in the fossilized fish vertebrae. Contrary to common opinion, the present findings suggest that the preservation of collagen in fossilized soft tissues is not rare. We propose that one of the essential factors controlling preservation of collagen is the establishment of a suitable microenvironment within the fossil, inhibiting diagenetic alteration including microbial decay.